Kesetaraan Hak Warga Kolok sebagai Wujud Integrasi Sosial Warga Desa Bengkala - Angelita, Chrisantya (Humanis; Vol 25 No 2 (2021)DO - 10.24843/JH.2021.v25.i02.p14, 2021)
Deaf mute villager in Bengkala village is called as kolok villager. In Bengkala Village, kolok villager as disabled community is not getting discriminated by society. This research intend to study about equality rights for kolok villager in Bengkala Village. Theory used in this study is Functionalism Structural Talcott Parsons. The research method are interview and observation. The result shows that kolok villager are accepted by Bengkala Village society. Because basically normal villager and kolok villager are related. The equality rights are art right, education right, economy right, and voting right.